Monitoring System Prototype Design at The Project Management Units - Sefhia Astri Yulika Purba; Edy Rahman Syahputra; Halim Maulana (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2022)
Project Management Unit of ERP (Enterprise Resource Planning) serves to limit, planning, forecasting, scheduling, organizing, directing, controlling, and closing projects. Technological development monitoring system and growing can be used to assist management in monitoring to ensure all activities conducted goes according to plan. The technology can be used as a media monitoring include web-based technology. The method used is by direct observation in ERP Project Management Unit, analyzing procedures and processes on the system is running, as well as describe the procedure using UML. To support the accuracy of the data, the research conducted by the method of literature, by searching for relevant information from various books and browsing the Internet. I also conduct experiments or in practice in the design and manufacture of prototype applications Project Management Monitoring System. The benefits of this research is to produce a new system in the form of application Project Management Web-based Monitoring System is capable of supporting high mobility of employees to report any activity that has been, is being, or will be done in realtime. The report was subsequently used as a basis for analyzing the shortcomings of the activities that have been done so that management can do forecasting activities that will be implemented in the future. From this research, the expected performance of the ERP Project Management Unit in monitoring projects can be more effective, efficient, and optimal